Peculiarities of statistical methodology of international comparisons on makrolevel - Kushchenko, Olena (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The article reveals the main principles and the essence of cross-country comparison of statistical indicators. It considers the necessity of multilateral comparisons in connection with the requirements of States, as well as statistical estimation of their competative abilieties in different spheres. Methodology of the given indexes makes the informational base necessory for taking correct managerial decisions.